1994
DOI: 10.1007/bf00666206
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry: Potential utility in monitoring drug effects in breast cancer

Abstract: Flow cytometric analysis of DNA ploidy and S-phase fraction are well recognized prognostic indicators in breast cancer. The present paper deals with the widening of the applications of flow cytometry to monitoring the effectiveness of antiestrogen therapy, detecting clonal selection and emergence of drug resistance, and monitoring chemosensitizing properties of drugs. Antiestrogen activity can be studied by DNA flow cytometry to address clinical research problems such as patient-specific pharmacokinetics, dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…FCM may be incorporated in a wealth of different studies, notably: cell cycle analysis (Sitton and Srienc, 2008;Calvert et al, 2008); apoptosis 4 (Lecoeur, 2002;Yasuda et al, 2005;Yasuhara et al, 2003) and stem cell investigations (Nolan and Yang, 2007;Castagnola et al, 2011); and drug effect trials (Koester et al, 1994;Morgan et al, 1989). Furthermore, FCM has been used in conjunction with other complementary modalities such as: photothermal and PA applications for the study of blood and lymph flows (Zharov et al, 2005(Zharov et al, , 2006b(Zharov et al, , 2007; applications in tumour analysis and fluorescence-based (Yi et al, 2006).…”
Section: Cytometric Methodsmentioning
confidence: 99%
“…FCM may be incorporated in a wealth of different studies, notably: cell cycle analysis (Sitton and Srienc, 2008;Calvert et al, 2008); apoptosis 4 (Lecoeur, 2002;Yasuda et al, 2005;Yasuhara et al, 2003) and stem cell investigations (Nolan and Yang, 2007;Castagnola et al, 2011); and drug effect trials (Koester et al, 1994;Morgan et al, 1989). Furthermore, FCM has been used in conjunction with other complementary modalities such as: photothermal and PA applications for the study of blood and lymph flows (Zharov et al, 2005(Zharov et al, , 2006b(Zharov et al, , 2007; applications in tumour analysis and fluorescence-based (Yi et al, 2006).…”
Section: Cytometric Methodsmentioning
confidence: 99%
“…Flow cytometry may be incorporated in a wealth of different studies, notably: cell cycle analysis [383,384]; apoptosis 7 [385][386][387] and stem cell investigations [388,389]; and drug effect trials [390,391]. Furthermore, flow cytometry has been used in conjunction with other complementary modalities such as: photothermal and photoacoustic applications for the study of blood and lymph flows (see Figure 30) [382,392,393]; applications in tumour analysis and fluorescence based breast cancer imaging [394][395][396][397]; Figure 29 Illustration of flow cytometric cell sorting [376].…”
Section: Cytometric Methodsmentioning
confidence: 99%
“…The C-erb-B2 gene, which is structurally related but different from the EGFR gene, is amplified and over expressed with an incidence of up to 32% in human primary breast tumors and has been correlated with poor overall survival and early relapse [6]. There are conflicting reports regarding the clinical significance of DNA flow cytometry measurements of ploidy status, while measurements of the S-phase fraction indicate an association with a high risk of tumor recurrence [1,7]. Quite a few potential prognostic para meters, including expression of estrogen-regulated proteins and proteases, amplification and/or overexpression of onco genes and growth factors and their receptors such as pS2, cathepsin D and EGFR, have so far been studied, but no con sensus exists regarding their interrelationships and prognostic value [8,9], Differences in assay methodology, in the various definitions used for positivity/negativity, in patients selection and use of systemic adjuvant treatment might have influenced the outcome of the mostly retrospective studies and could pro vide possible explanations for the discrepant results reported [10][11][12], The aim of the present prospective study was to inves tigate the relationship between some of these factors such as pS2 protein, cathepsin D and EGFR and established prog nostic factors and to evaluate their potential prognostic value in early recurrence of breast cancer.…”
Section: Methodsmentioning
confidence: 99%